CIAPIN1 promotes survival, proliferation, migration and glycolysis of endometrial cancer cells through PI3K/Akt pathway - Huanmei Sun; Juan Shao; Yingchun Duan; Jiashi Gu (Scientific Reports)
Abstract Cytokine-induced apoptosis inhibitor 1 (CIAPIN1) is a protein that regulates apoptosis and programmed cell death. This study aimed to assess the potential function of this molecule in curbing the proliferation, migration, and glycolysis of endometrial cancer cells and to elucidate its molecular mechanism. We obtained endometrial cancer tissue samples from our hospital to examine the CIAPIN1 expression levels. The human endometrial cancer cell line Ishikawa was transfected with CIAPIN1 siRNA. mRNA and protein expression were then measured using RT-qPCR and Western blotting techniques. CIAPIN1 expression was elevated in both endometrial cancer tissues and serum. CIAPIN1 overexpression enhances cell proliferation and migration, whereas CIAPIN1 silencing (siRNA) increases apoptosis. Mechanistically, CIAPIN1 inhibition elevated reactive oxygen species (ROS) production and oxidative stress, as evidenced by increased malondialdehyde (MDA) and reduced superoxide dismutase (SOD) and catalase (CAT) levels. Furthermore, CIAPIN1 promoted glycolysis via the PI3K/Akt pathway, increasing glucose consumption, lactate secretion, ATP production, and the expression of glycolytic enzymes (PKM2 and LDHA). PI3K inhibition (LY294002) reversed these effects, confirming the pathway dependency. These findings highlight CIAPIN1 as a potential oncogenic driver in EC, enhancing tumor progression through PI3K/Akt-mediated glycolysis and oxidative stress modulation. Targeting CIAPIN1 may represent a novel therapeutic strategy for EC.